Renovation work process at Pusat Ilmu, Headquaters of Mardi Serdang, Selangor / Ainnur Amirah Roslan - Roslan, Ainnur Amirah (Universiti Teknologi Mara, Perak, 2014)
In growing development nowadays, everyone compete to develop something good and sell their service and goods. The minor Renovation Work has give a chance to small companies to handle it. MARDI engineering department goal is to produce or construct the service for great satisfaction and a good feedback from their client. We ensure that we provide a first class building service to all our client. We advise our outsource contractor to deliver guarenteed start and realistics completion dates, our commitment to a clean and tidy work and give disturbance to occupant around and we have the dedicated team whilst also ensuring full project management. The success of the building not only comes from the comitment and dedication of the team, its also due to the relationship we have with the clients. We have received the great response and feedback from our customers and outsource contractor. Although MARDI does not development agencies like JKR, but this division was doing his job as a custodian and guardian of all buildings owned by MARDI with excellently.